ON A GENERALIZATION OF THE GUMBEL DISTRIBUTION - Ahmed Hurairah; Noor Akma Ibrahim; Isa bin Daud; Kassim Haron (Program Studi Statistika Unisba, 2003)
In the paper, we proposed a generakization of the gumbel distribution. Simpel properties of the distribution arestudied.